Evaluating microbiological safety and associated handling practices of butchery-sold meat in Nairobi, Kenya - Koech, Patricia Cherotich; Ogutu, Winnie Aketch; Ochieng, Linnet; Grace, Delia; Gitao, George; Bebora, Lilly; Korir, Max; Mutua, Florence; Moodley, Arshnee (Frontiers in Sustainable Food Systems, 2024)
Approximately 70% of diarrheal cases in Kenya are attributed to ingestion of contaminated food and water and cause costs an estimated cost of 1 billion USD due to morbidity total people loss of productivity loss and cost of treatment of these diseases. This study aimed to assess the levels of microbiological contamination of meat sold in selected butcheries in Nairobi and the handling practices of butcher shop attendants. A cross-sectional study design was used during which 200 meat samples were collected, and meat handling practices were observed. Total coliforms and Escherichia coli were enumerated using 3M TM Petrifilm® count plates, while direct plating on chromogenic Salmonella agar plates was used to isolate Salmonella spp. Additionally, quantification identification of tetracyclineand cefotaxime-resistant Enterobacteriaceae was done on agar plates containing the respective antibiotics. Bacterial species were confirmed by Matrix-Assisted Laser Desorption/Ionization-Time of Flight mass spectrometry. Eighty-four percent and 72% Seventy two percent and 84% of the samples had E. coli and total coliforms respectively and E. coli above the acceptable regulatory limits (i.e. tTotal coliforms >361 CFU/g, E. coli >100 CFU/g, Total coliforms >361 CFU/g,) respectively as per the Kenya Bbureau of Sstandards, South African microbiological standardsCodex Alimentarius Commission and the European Union standards. No Salmonella was detected. Enterobacteriaceae resistant to tetracycline and cefotaxime were detected in 35% and 9.5% of the samples respectively. Eighty-five percent of the butcher shop attendants neither washed their hands before nor after handling the meat, 91% handled money while selling meat concurrently, and 99% did not wear gloves while handling meat. These poor meat handling practices coupled with the presence of microbial loads above the regulatory acceptable limits imply an increased risk of foodborne illness to consumers. Therefore, there is an urgent need for education of butcher shop attendants on appropriate handling of meat, highlighting the importance of good hygienic practices and their relationship to food safety, and provision of incentives for behavior change. This study is important and serves to inform policymakers in the identification of key control points for designing meat safety intervention(s).